Pharmacokinetics and Bioequivalence Evaluation of Cyclobenzaprine Tablets - Brioschi, Tatiane Maria de Lima Souza (Hindawi Publishing Corporation, 2013)
The purpose of this study was to investigate cyclobenzaprine pharmacokinetics and to evaluate bioequivalence between two different tablet formulations containing the drug. An open, randomized, crossover, single-dose, two-period, and two-sequence design was employed. Tablets were administered to 23 healthy subjects after an overnight fasting and blood samples were collected up to 240 hours after drug administration. Plasma cyclobenzaprine was quantified by means of an LC-MS/MS method. Pharmacokinetic parameters related to absorption, distribution, and elimination were calculated. Cyclobenzaprine plasma profiles for the reference and test products were similar, as well as absorption pharmacokinetic parameters AUC (reference: 199.4 ng∗h/mL; test: 201.6 ng∗h/mL), C(max) (reference: 7.0 ng/mL; test: 7.2 ng/mL), and T (max) (reference: 4.5 h; test: 4.6 h). Bioequivalence was evaluated by means of 90% confidence intervals for the ratio of AUC (93%–111%) and C (max) (93%–112%) values for test and reference products, which were within the 80%–125% interval proposed by FDA. Cyclobenzaprine pharmacokinetics can be described by a multicompartment open model with an average rapid elimination half-life (t ((1/2)β)) of 3.1 hours and an average terminal elimination half-life (t ((1/2)γ)) of 31.9 hours.